Making Transgenic C. elegans with Polycistronic mCherry Vector - Farka, Dominik (Jihočeská univerzita, 2012)
Creation of transgenic animals has become a popular method to analyse gene function. In the nematode Ceanorhabditis elegans transformation is widely used and can be achieved by microinjection. For functional analyses, transgene constructs typically contain a promoter driving the expression of the protein of interest that is fused to a fluorescent protein. However, as this fusion of proteins can lead to misfolding of the protein of interest and may not reflect proper function, a modification of the expression vector has been developed; introducing a short sequence of non-coding DNA in-between the sequences of the two proteins and making the construct compatible with a polycistronic operon system. In this study, four different polycistronic constructs were introduced into C. elegans by means of microinjection in order to provide new tools for the analyses of gene function. Tissue specific promoters wrt-2 (seam cells), grl-21 (hyp7), and egl-17 (vulval precursor cells) were used to over-express either NHR-25 or SMO-1 in the corresponding tissues and the expression was visualized by independently translated mCherry red fluorescent. 10 independent transformed C. elegans strains were established and corresponding tissue-specific promoter activities were confirmed. Furthermore, in some cases, ectopic behaviour was observed e.g. ectopic mCherry expression in different tissues or specific cell differentiation defects that was most likely caused by the overexpression of NHR-25 or SMO-1. This study was the first case in our laboratory to generate transformed C. elegans utilizing the polycistronic mCherry vector system. New genetic tools were introduced in the laboratory useful for further analyses of gene function.
Making Transgenic C. elegans with Polycistronic mCherry Vector
Keywords: polycistronic system; operon; genetics; molecular biology; C. elegans; transgenic; microinjection; NHR-25; SMO-1; tissue specific promoters; polycistronic system; operon; genetics; molecular biology; C. elegans; transgenic; microinjection; NHR-25; SMO-1; tissue specific promoters